Biomolecule-corona formation confers resistance of bacteria to nanoparticle-induced killing: Implications for the design of improved nanoantibiotics. (February 2019) - Siemer, Svenja; Westmeier, Dana; Barz, Matthias; Eckrich, Jonas; Wünsch, Désirée; Seckert, Christof; Thyssen, Christian; Schilling, Oliver; Hasenberg, Mike; Pang, Chengfang; Docter, Dominic; Knauer, Shirley K.; et al.
Abstract: Multidrug-resistant bacterial infections are a global health threat. Nanoparticles are thus investigated as novel antibacterial agents for clinical practice, including wound dressings and implants. We report that nanoparticles' bactericidal activity strongly depends on their physical binding to pathogens, including multidrug-resistant primary clinical isolates, such as Staphylococcus aureus, Klebsiella pneumoniae or Enterococcus faecalis . Using controllable nanoparticle models, we found that nanoparticle-pathogen complex formation was enhanced by small nanoparticle size rather than material or charge, and was prevented by 'stealth' modifications. Nanoparticles seem to preferentially bind to Gram-positive pathogens, such as Listeria monocytogenes, S. aureus or Streptococcus pyrogenes, correlating with enhanced antibacterial activity. Bacterial resistance to metal-based nanoparticles was mediated by biomolecule coronas acquired in pathophysiological environments, such as wounds, the lung, or the blood system. Biomolecule corona formation reduced nanoparticles' binding to pathogens, but did not impact nanoparticle dissolution. Our results provide a mechanistic explanation why nano-sized antibiotics may show reduced activity in clinically relevant environments, and may inspire future nanoantibiotic designs with improved and potentially pathogen-specific activity.